Loyalty and inheritance in the central newscasts of Chilean television - Marshall, Pablo; Arnold, Ignacio (Estudios de Administración, 2003)
This paper considers the loyalty and inheritance effects in the news program of the open television in Chile. The study uses data from the People Meter system to measures the loyalty and inheritance effects concepts for different television channels and different socio-demographic groups. The results of the study show significant differences in loyalty and inheritance effects across channels and sociodemographic groups. The paper represents a contribution, not only for this specific data set. It also gives a methodological contribution in the analysis of other data sets from the People Meter system.